Index Admission Percutaneous Coronary Intervention versus Pharmaco-invasive Strategy for Patients with Acute ST-Elevation Myocardial Infarction: A Tertiary Centre-based Study - Mohammed, Muaath A. H; W Isa, WYH; Yusof, Z (IIUM Medical Journal Malaysia, 2022)
Introduction: Pharmaco-invasive strategy is a standard of care in patients with ST -elevation myocardial infarction (STEMI), but the optimal timing may not be achieved due to limitations. Thus, a large number of patients underwent percutaneous coronary intervention (PCI) at a later timing during their index hospitalisation. However, small evidence is available on the outcome of this strategy. This study aimed to compare the clinical outcomes of PCI during index admission with a pharmaco-invasive strategy for patients with STEMI. Material&Methods: This retrospective cohort study was conducted at a tertiary centre. Medical records of all STEMI patients who were treated by PCI from January 2013 to March 2018 were retrieved. The clinical outcomes of the study were the rate of major adverse cardiac event (MACE) and major bleeding at 30 days and 6 months post PCI. Results: A total of 91 STEMI patients were analysed. Twenty-nine (31.9%) patients were treated by pharmaco-invasive strategy, and 62 (68.1%) patients underwent PCI during their index admission. At 30 days post PCI, the rates of MACE in the pharmaco-invasive and PCI during index admission group were 10.7% and 10.3%, respectively (p = 0.958). The rates at 6 months were 8.3% and 7.8% (p = 0.942). The rates of major bleeding at 30 days were one (3.6%) and none (p = 0.151). By contrast, the rate at six months was only one (2.0%) for the PCI during index admission group. Conclusions: PCI during index admission may had similar clinical outcomes to pharmaco-invasive strategy.